Pengaruh Gerak Ritmik Terhadap Kecerdasan Kinestetik Anak Usia 5-6 Tahun di TK Negeri Pembina Ki Hajar Dewantoro Kecamatan Kota Selatan Kota Gorontalo - Nurjaini A. Kabulu; Icam Sutisna; Sri Wahyuningsi Laiya (Institut Nalanda, 2024)
This research aimed to determine the influence of rhythmic movement on the kinesthetic intelligence of children aged 5-6 years. The research was an experimental study (one group pretest-posttest). The population consisted of 74 children, with a sample of 24 children from group B3, aged 5-6 years, at TK Negeri Pembina Ki Hajar Dewantoro. The data analysis technique was supported by statistical data processing. The research results showed an increase in the average pre-test score, with a mean of 12.95 and a standard deviation of 2.45. Meanwhile, the average post-test score was 25.87, with a standard deviation of 4.01. These results indicate a significant effect before and after the treatment. Based on the t-test, the calculated tcount= 13.44, while the table t-table at (a) = 0.05 was 2.064. Since tcount > ttable; 13.44>2.064, Ho is rejected, and Hi is confirmed. If tcount > ttable, it means there is an influence of rhythmic movement on the kinesthetic intelligence of children aged 5-6 years at TK Negeri Pembina Ki Hajar Dewantoro, Kota Selatan District, Gorontalo City.